Faktor-Faktor yang Berhubungan dengan Kepatuhan Lansia dalam Mengonsumsi Obat Hipertensi - Cut Rahmayani; Wardati Wardati; Agustina Agustina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Hypertension is a chronic disease commonly found among the elderly and requires long-term treatment with a high level of medication adherence. This study aimed to determine the relationship between family support, knowledge, and sociodemographic factors with medication adherence among elderly patients with hypertension at Idi Rayeuk Health Center. This study used a cross-sectional design. The population consisted of 694 elderly individuals, with a sample of 87 respondents selected using accidental sampling technique. Data were collected through interviews using a questionnaire administered via Google Forms. Data analysis was performed using SPSS version 25, with chi-square test for bivariate analysis and ordinal logistic regression for multivariate analysis (α = 0.05). The results showed that only 52.9% of respondents were adherent to antihypertensive medication. Bivariate analysis indicated that all variables were significantly associated with medication adherence. Multivariate analysis revealed that age, education level, family support, knowledge, and self-efficacy were significantly associated with medication adherence, while gender and marital status were not. In conclusion, family support, knowledge, and self-efficacy play an important role in improving medication adherence among elderly patients with hypertension.